2022
DOI: 10.1093/mnras/stac2099
|View full text |Cite
|
Sign up to set email alerts
|

Energy balance and Alfvén Mach numbers in compressible magnetohydrodynamic turbulence with a large-scale magnetic field

Abstract: Energy equipartition is a powerful theoretical tool for understanding astrophysical plasmas. It is invoked, for example, to measure magnetic fields in the interstellar medium (ISM), as evidence for small-scale turbulent dynamo action, and, in general, to estimate the energy budget of star-forming molecular clouds. In this study we motivate and explore the role of the volume-averaged root-mean-squared (rms) magnetic coupling term between the turbulent, $\delta \mathrm{{\boldsymbol {\mathit {B}}}}$ and large-sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 114 publications
3
8
0
Order By: Relevance
“…For turbulent as well as for mean magnetic field strengths, we find an average scaling relation of B ∝ n 0.58 H . We confirm the models by Federrath (2016), Beattie et al (2020), and Beattie et al (2022) with the prediction of a critical transition for the magnetic-field evolution that imposes upper limits on the strengths of mean-field normalized magnetic field fluctuations. 2022).…”
Section: Results From the St Solutionsupporting
confidence: 86%
See 3 more Smart Citations
“…For turbulent as well as for mean magnetic field strengths, we find an average scaling relation of B ∝ n 0.58 H . We confirm the models by Federrath (2016), Beattie et al (2020), and Beattie et al (2022) with the prediction of a critical transition for the magnetic-field evolution that imposes upper limits on the strengths of mean-field normalized magnetic field fluctuations. 2022).…”
Section: Results From the St Solutionsupporting
confidence: 86%
“…( 11) to (13). Furthermore, only B POS = B ST from the ST solution shows an upper limit to |δB|/|B POS | for the expected equilibrium between turbulent and mean magnetic fields as predicted by Federrath (2016), Beattie et al (2020), andBeattie et al (2022). Our results strongly support compressible quasi-static fluctuation models (Fig.…”
Section: Uncertainties and Biasessupporting
confidence: 82%
See 2 more Smart Citations
“…In this case, the volume-averaged coupling-term magnetic energy is 0 by definition (Zweibel and McKee, 1995;Liu et al, 2022), which should not be used in analyses. Several numerical studies (Federrath, 2016;Beattie et al, 2020;Beattie et al, 2022) have suggested that the volume-averaged RMS coupling-term magnetic energy fluctuation should be studied instead of the volume-averaged coupling-term magnetic energy. With non-self-gravitating sub-Alfvénic simulations, they found that the coupling-term field energy fluctuation is in equipartition with the turbulent kinetic energy within the whole simulation box.…”
Section: Sub-alfvénic Casementioning
confidence: 99%